Planned spatial arrangement of high-speed railway lines in Poland - Juliusz Engelhardt (Przegląd Komunikacyjny)
Abstract: The article analyzes the main directions of long-distance rail transport in Poland, confronting them with the main directions of population movements in individual road transport, which allowed for the formulation of a general conclusion as to the polycentric rather than monocentric system of the Polish land transport network, in which the main passenger flows are closed in two circles. The smaller circle is formed by Warsaw, Łódź, Poznań and Bydgoszcz with Toruń, while the larger one is defined by the main cities of northern, eastern, southern and western Poland. On the basis of this analysis, a general recommendation was formulated that when designing the spatial and geographical layout of new high-speed railway lines, the layout of passenger flows inside the country should also be taken into account. The new concepts of the geographic route of high-speed railway lines related to the railway component of the project to build the Central Communication Port (CPK) in Poland do not fully take into account this postulate because they have been completely subordinated to the function of transporting and transporting passengers to the planned central airport. In the further part of the article, after a critical analysis of the assumed spatial and geographical routes of new high-speed lines Warsaw - Łódź - Poznań / Wrocław, the CPK - Płock - Grudziądz - Gdańsk line and the designed sections of high-speed lines for the CPK - Rzeszów transport route, specific corrections of their spatial routes are proposed. Keywords: Railway development in Poland; Railway component of the CPK project; High Speed Railways